Suicidal ideation among MSM in three West African countries: Associations with stigma and social capital. (September 2016) - Stahlman, Shauna; Grosso, Ashley; Ketende, Sosthenes; Pitche, Vincent; Kouanda, Seni; Ceesay, Nuha; Ouedraogo, Henri G; Ky-Zerbo, Odette; Lougue, Marcel; Diouf, Daouda; Anato, Simplice; Tchalla, Jules; et al.
Background: Suicidal ideation is understudied among men who have sex with men (MSM) across Sub-Saharan Africa. Aims: This study aimed to explore social capital and sexual behavior stigma associated with suicidal ideation among MSM in the West African nations of The Gambia, Burkina Faso and Togo. Methods: Participants were recruited using respondent-driven sampling and snowball sampling across multiple cities ( n = 1555) from July 2011 to August 2013. During a single study visit, participants completed a survey. Logistic regression models were used to assess bivariate and multivariable associations with suicidal ideation. Results: The prevalence of lifetime suicidal ideation was 13% overall and ranged 6%–17% across study sites. After adjusting for potential confounders, MSM who reported stigma as a result of having sex with men were more likely to report suicidal ideation. Physical and sexual violence was strongly associated with suicidal ideation, including being physically harmed (adjusted odds ratio (aOR) = 2.94, 95% confidence interval (CI) = 1.91, 4.52), tortured (aOR = 3.86, 95% CI = 2.17, 6.86) and raped (aOR = 3.07, 95% CI = 2.05, 4.60). In contrast, increasing social participation with the broader community was associated with decreased report of suicidal ideation (aOR = 0.91, 95% CI = 0.85, 0.99). Conclusion: Sexual behavior stigma should be addressed to improve mental health among MSM in Western Sub-Saharan Africa.